Sharia Mediation as an Alternative Model of Sharia Banking Dispute Resolution - Haeratun, Haeratun; Hariati, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The resolution of conflicts or disputes in society refers to the principle of freedom that benefits both parties. The parties can offer dispute resolution options with intermediaries of community leaders, banking mediators, or mediators from Bank Indonesia, especially related to Islamic banking disputes. Out-of-court mediation is a process of peaceful dispute resolution that is commonly used by the community and mediated by a neutral third party. The purpose of this study is, first, to explain the model of Sharia banking dispute resolution through Sharia mediation outside the court, second, to explain the implementation in the practice of Sharia banking dispute resolution outside the court. Research methods include normative/doctrinal research type. The result of this study is that the Sharia banking dispute resolution model through Sharia mediation in a non-litigation manner is considered to be more able to accommodate some of the weaknesses of the litigation model and has provided a better solution because mediation has many elements in common with the consensus deliberation mechanism which is the spirit of dispute resolution in Indonesian society. Meanwhile, the data collection technique in this study is carried out using several stages starting with the collection of secondary data in the form of primary legal materials and secondary legal materials related to the settlement of Islamic banking disputes through sharia mediation. These legal materials were obtained through the search of several laws and regulations related to the settlement of Islamic banking disputes through sharia mediation on a non-litigation basis.